Spatio-temporal distributions of chlorofluorocarbons and methyl iodide in the Changjiang (Yangtze River) estuary and its adjacent marine area. Issue 1 (15th February 2016) - Yuan, Da; Yang, Gui-Peng; He, Zhen
Abstract: Temporal and spatial distribution patterns of volatile halogenated organic compounds (VHOCs), such as dichlorodifluoromethane (CFC-12), trichlorofluoromethane (CFC-11), trichlorotrifluoroethane (CFC-113), and methyl iodide (CH3 I), in the Changjiang (Yangtze River) estuary and its adjacent marine area were measured during two cruises from 21 February to 10 March 2014 and from 10 to 21 July 2014. VHOC concentrations showed seasonal variation with higher values during winter. VHOC distributions evidently decreased along the freshwater plume from the river mouth to the open sea and from inshore to offshore regions. VHOC distributions were obviously influenced by the Changjiang runoff, anthropogenic inputs, and biological release of phytoplankton. The study area was a net sink for CFC-12 and CFC-11, but a net source for atmospheric CH3 I during the study periods. Highlights: Distributions of VHOCs in the Changjiang estuary were studied for the first time. CFCs and CH3 I exhibited significant spatio-temporal variations in the study area. Terrestrial input was the primary contributor of CFCs in the Changjiang estuary. Biological production contributed to the enhanced CH3 I concentrations. Changjiang estuary and its adjacent area were a net source of atmospheric CH3 I.